Effects of Glycated Hemoglobin Level on Bone Metabolism Biomarkers in Patients with Type 2 Diabetes Mellitus - Zhao H (Dove Medical Press, 2020)
Hang Zhao,1 Cuijuan Qi,1 Chong Zheng,2 Kexin Gan,1 Luping Ren,1,* Guangyao Song1,* 1Endocrinology Department, Hebei General Hospital, Hebei 050051, People’s Republic of China; 2Pediatric Orthopaedics, Shijiazhuang the Third Hospital, Hebei 050011, People’s Republic of China*These authors contributed equally to this workCorrespondence: Luping Ren Email renluping1122@163.comPurpose: We aimed to determine the relationship between the levels of glycated hemoglobin (HbA1c) and biomarkers of bone metabolism in patients with type 2 diabetes mellitus (T2DM), and whether HbA1c independently influences any of these biomarkers.Patients and Methods: A cohort study of 240 patients with T2DM was performed. Serum was obtained and used to measure HbA1c, total cholesterol (TC), triglycerides, high-density lipoprotein-cholesterol, low-density lipoprotein-cholesterol (LDL-C), very-low-density lipoprotein-cholesterol, apolipoprotein A1 (ApoA1), apolipoprotein B (ApoB), total protein, albumin, blood urea nitrogen (BUN), creatinine, serum 25-hydroxyvitamin D (25OHD), osteocalcin (OC), β-C-terminal cross-linked telopeptide of type I collagen (β-CTX), procollagen type 1 N-terminal propeptide (P1NP), or parathyroid hormone (PTH) concentrations. The participants were divided into three study groups according to HbA1c level: < 7%, 7– 9% and ≥ 9%. Chi-square testing and one-way analysis of variance were used to compare groups. The relationships between HbA1c and bone metabolism biomarker values were analyzed using linear correlation analysis and multiple linear regression analysis.Results: Age, duration of T2DM, and the concentrations of TC, LDL-C, apolipoprotein B, albumin, and BUN showed significant difference among the < 7%, 7– 9% and ≥ 9% HbA1c groups. Of the bone metabolism biomarkers, there were significant differences in serum 25-hydroxyvitamin D (25OHD) and osteocalcin (OC) among the groups. The correlation coefficients (r) for the relationships of HbA1c with 25OHD and OC were − 0.200 and − 0.183, respectively (P < 0.05). Regardless of adjustment for none, some, or all of the confounding factors (age, sex, and duration of T2DM), the 25OHD and OC concentrations were significantly lower in the HbA1c ≥ 9% group than in the HbA1c < 7% group. HbA1c showed no relationship with β-CTX, PINP, or PTH.Conclusion: T2DM patients with poorer glycemic control had lower concentrations of serum 25OHD and OC, suggesting that HbA1c is an independent risk factor for low 25OHD and OC.Keywords: diabetes mellitus type 2, bone metabolism, glycated hemoglobin